PERAN KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAK ASASI MANUSIA TERHADAP PENDAFTARAN INDIKASI GEOGRAFIS - Sipayung, Erick Junata (Universitas Internasional Batam, 2020)
Indonesia is a country rich in biological natural resources which is spread throughout the region, including the Riau Islands Province. Geographical location surrounded by almost 90% (ninety percent) of the sea area, it indirectly indicates the potential of Geographical Indications that are spread in 7 (seven) districts/ cities in Riau Islands. Directorate General of Intellectual Property through the Regional Office of the Ministry of Law and Human Rights has committed to continue to explore the IG potential in each region determined through the Annual Performance Target. IG legal protection can only be given if an item or product has been registered, for example